Diversity of tree communities and its relationships with soil properties in a peat swamp forest in Pahang, Peninsular Malaysia. - Said, Mohd Nizam; P., Ismail; A., Latiff; I., Shamsudin; Ibrahim, Faridah Hanum (Enviro Media, 2009)
A study was conducted in a peat swamp forest at Pekan Forest Reserve, Pahang in Peninsular Malaysia with objectives to assess tree diversity and to examine relationships between tree communities and its soil characteristics. Tree species inventory was conducted in a one-hectare plot at three selected forest compartments viz. Compartment 100, 156 and 200, whilst soil samplings were carried out in nine selected subplots of each compartment, totalling 27 subplots for soil analyses. The measured soil variables include peat depth, soil pH, organic matter content, available Mg, P and K, total inorganic-N, total cation exchange capacity (CEC) and content of clay and silt. A total of 376 trees were enumerated in the plot at Compartment 100 which comprised of 49 species in 38 genera and 26 families. Compartment 156 contained a composition of 68 tree species in 49 genera and 28 families from a total of 557 enumerated trees whilst Compartment 200 recorded 555 trees which comprised of 100 tree species in 76 genera and 38 families. Guttiferae was the most speciose family in plots at Compartment 100 and 200, while Burseraceae was the most speciose in Compartment 156. The most important species in Compartments 100. 156 and 200 were Colophyllum ferrugenium var. ferrugenium, Stemontirus secundiflorus and Modhuca motleyona, respectively. The Shannon- Weiner Diversity Index (H') of tree species were different significantly between the study plots with H' values of 3.15, 3.61 and 4.12 for the plots in Compartments 100, 156 and 200, respectively. Soils of the study site were acidic and showed peat and silty clay texture, whilst available nutrients were of low to high concentrations. A floristic compositional pattern was observed among all surveyed subplots which were correlated to the edaphic variables as revealed by canonical correspondence analysis. Peat depth, soil pH, total inorganic-N, potassium, magnesium and phosphorus appear to be the principal environmental determinants of tree communities in the study plots.